Pemanfaatan Tradisi Lisan Senjang Musi Banyuasin Sumatra Selatan Sebagai Identitas Kultural - Arif Ardiansyah (Universitas PGRI Palembang, 2016)
This research examines Senjang as the Oral Tradition Musi Banyuasin South Sumatra. This study used qualitative research with the ethnographic approach. The results showed that the oral tradition of Senjang is as media forms of cultural arts that connect parents with young generation or it can be also between the society and government in delivering the aspiration such as the advice, criticism or even the delivery strategy of happiness feeling. Some attempts have been made to preserve, utilize and develop Senjang tradition through schools, galleries and arts tradition festival. Senjang is present in traditional events such as marriage, thanksgiving, and the other which becomes a cultural identity of Musi Banyuasin.Keywords: Oral Tradition, Senjang, Cultural Identity and Musi Banyuasin